Does parental support moderate the effect of children's motivation and self-efficacy on physical activity and sedentary behaviour?. (September 2017) - Gillison, F.B.; Standage, M.; Cumming, S.P.; Zakrzewski-Fruer, J.; Rouse, P.C.; Katzmarzyk, P.T.
Abstract: Objectives: 1) To test whether parental support moderates the direct effects of children's motivation and self-efficacy on objectively measured moderate-vigorous physical activity (MVPA) and sedentary time. 2) To explore differences in the relationships between boys and girls. Design: Cross-sectional observational study. Method: Data were collected from 430 9–11 year old UK children and their parents; parents self-reported on the support they provided to their children to be active (through providing transport, encouragement, watching, or taking part with their child), and children self-reported their motivation and self-efficacy towards exercise. MVPA and sedentary time were measured using accelerometers. Results: Both parent- and child-level factors were largely positively associated with children's MVPA and negatively related to sedentary time. There was no evidence of a moderation effect of parental support on MVPA or sedentary time in boys. Parental provision of transport moderated the effect of girls' motivation on week-day MVPA; more motivated girls were less active when transport was provided. Transport and exercising with one's child moderated the effect of motivation and self-efficacy on girls' sedentary time at weekends; more motivated girls, and those with higher self-efficacy were less sedentary when parents provided more frequent transportation or took part in physical activity with them. Conclusions: The results largely supported a model of the independent effects of parent and child determinants for moderate-to-vigorous physical activity, but there was evidence that some types of parent support can moderate sedentary time in girls. Further research is needed to explore the causal pathways between the observed cross-sectional results. Highlights: Parental support for physical activity does not moderate the effects of boys' motivation on MVPA. More motivated girls were less active when transport was provided by parents at weekends. More motivated girls were less sedentary at weekends when parent support was greater. Girls with higher self-efficacy were less sedentary at weekends when parent support was greater.